Holographic photonic crystals with diamond symmetry - Sharp, D; Turberfield, A; Denning, R (2003)
We explore the analytical design of high-symmetry photonic crystals made by holographic lithography. We show how holographic lithography may be used to produce diamond-like photonic crystals that have a full, three-dimensional photonic band gap at a refractive index contrast equal to the lowest yet published.